Triassic lithostratigraphy of the jameson land basin (Central east greenland), with emphasis on the new fleming fjord group - Clemmensen, Lars B.; Kent, Dennis V.; Mau, Malte; Mateus, Octávio; Milàn, Jesper (Bulletin of the Geological Society of Denmark, 2020)
8410, the Independent Research Fund Denmark and GEUS. Constructive comments from Gunver K. Pedersen (Co-editor), Gregers Dam (reviewer), and Atle Mork (reviewer) helped to improve the paper. The lithostratigraphy of the Triassic deposits of the Jameson Land Basin in central East Greenland is revised. The new Scoresby Land Supergroup is now composed of the Wordie Creek, Pingo Dal, Gipsdalen and Fleming Fjord Groups. This paper only deals with the lithostratigraphy of the late Early-Late Triassic continental deposits of the latter three groups with emphasis on the vertebrate-bearing Fleming Fjord Group. The new Pingo Dal Group consists of three new formations, the Rødstaken, Paradigmabjerg and Klitdal Formations (all elevated from members), the new Gipsdalen Group consists of three new formations, the Kolledalen, Solfaldsdal (with the new Gråklint Member) and Kap Seaforth Formations (all elevated from members), and the new Fleming Fjord Group is subdivided into three new formations, the Edderfugledal, Malmros Klint and Ørsted Dal Formations (all elevated from members). The Edderfugledal Formation contains two cyclic bedded, lacustrine members, a lowermost Sporfjeld Member (elevated from beds), and an uppermost Pingel Dal Member (elevated from beds). The lacustrine red beds of the Malmros Klint Formation are not subdivided. The lacustrine and fluvial Ørsted Dal Formation contains three new members. In the eastern and central part of the basin, the formation is initiated by cyclic bedded, red lacustrine mudstones of the Carlsberg Fjord Member (elevated from beds), while in the northwestern part of the basin the lowermost part of the formation is composed of grey fluvial conglomerates and sandstones with subordinate red mudstones of the Bjergkronerne Member (elevated from beds). The uppermost part of the formations in most of the basin is composed of cyclic bedded, variegated lacustrine mudstones and grey to yellowish marlstones of the Tait Bjerg Member (elevated from beds). The sediments in the Fleming Fjord Group ...